The Effect of Abdominal Stretching Exercise on Reducing the Intensity of Dysmenorrhea Pain - Sagita, Andes Julia; Novianti; Yusanti, Linda; Ramadhaniati, Fitri; Asmariyah; Yulyani, Linda (Journal of Health Sciences and Medical Development, 2024)
Dysmenorrhea is a gynecological complaint that occurs due to an imbalance in the hormone progesterone, resulting in pain that women often experience during menstruation.   One non-pharmacological way to deal with dysmenorrhea pain is to do abdominal stretching exercises. This study aimed to determine the effect of abdominal stretching exercise on reducing the intensity of dysmenorrhea pain in students of the Midwifery Diploma Study Program (MDSP), at Bengkulu University. This research was a pre-experimental study with a one-group pre-test and post-test design, involving 57 respondents who experienced moderate-category primary dysmenorrhea. Samples were taken using a random sampling technique. Data was collected using Standard Operational Procedures for abdominal stretching exercises and the Wong-Baker pain rating scale to determine the scale of dysmenorrhea pain. The results of data analysis using the Wilcoxon test showed p-value = 0.000 with a significance level of α = 0.05. This indicates an effect of abdominal stretching exercises on reducing dysmenorrhea in students of the MDSP.